2011
DOI: 10.1209/0295-5075/94/17003
|View full text |Cite
|
Sign up to set email alerts
|

Partial swapping of Fano resonance and bound states in continuum in a correlated double-quantum-dot system

Abstract: We study the partial swapping of the Fano resonance in a correlated double-quantumdot (DQD) system connected to normal leads by employing the Keldysh non-equilibrium Green function technique in a Coulomb blockade regime. Two types of asymmetries have been considered which occurs when the DQD system undergoes transition from symmetric parallel to i) series and ii) T-shape geometries. It is found that both types of asymmetries exhibit swapping on varying the interdot Coulomb interaction (U12), however, mostly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Thus, we expect that in this kind of symmetric configuration, independently of other effects such as electron correlations, BICs should exist and produce an enhancement of the figure of merit if the symmetry of the potentials is slightly broken by external manipulation. Indeed, there are previous studies showing that electron-electron interactions do not affect the existence of BICs in similar systems, albeit much simpler in geometry [50][51][52], so we foresee that our results are robust to this respect. We expect that our work will stimulate the search of thermoelectric devices in which quantum interference effects be exploited to improve the thermoelectric efficiency of nanoscale systems.…”
Section: Summary and Final Remarkssupporting
confidence: 58%
“…Thus, we expect that in this kind of symmetric configuration, independently of other effects such as electron correlations, BICs should exist and produce an enhancement of the figure of merit if the symmetry of the potentials is slightly broken by external manipulation. Indeed, there are previous studies showing that electron-electron interactions do not affect the existence of BICs in similar systems, albeit much simpler in geometry [50][51][52], so we foresee that our results are robust to this respect. We expect that our work will stimulate the search of thermoelectric devices in which quantum interference effects be exploited to improve the thermoelectric efficiency of nanoscale systems.…”
Section: Summary and Final Remarkssupporting
confidence: 58%
“…In contrast, the results obtained at low temperatures are associated with charge fluctuations in the QD1 "induced" by the variation of the quantum tunneling between the QD1 and the conduction channel (hybridization V QD1 ). In this case, the quasi-BIC associated with the enhancement of the thermoelectric efficiency is linked to asymmetries in the coupling between the QDs and the conduction channel, which originates a Fano character for the resonances, analogously to the described by Rajput et al [67].…”
Section: Bics Linked To the Enhancing Process Of Zt : High Temperatur...mentioning
confidence: 68%
“…To check the appearance of BICs, at low temperatures, we introduce an asymmetry in the hybridizations and maintain fixed the hybridization V QD2 and vary V QD1 . As demonstrated in reference [67], in the DQD geometry, the formation of BICs results from an interplay of correlation effects and asymmetries in dot-lead couplings.…”
Section: Bics Linked To the Enhancing Process Of Zt : Low Temperature...mentioning
confidence: 87%
“…Interestingly, controlling the size of one of the quantum dots makes the electron flow or get trapped inside the dots. BICs were also found in parallel doublequantum-dot systems [13] and they were found to be robust even if electron-electron interaction is taken into account [14]. Recently, González et al have demonstrated that not only quantum dots based on semiconductor materials but also on graphene can support BICs [15].…”
mentioning
confidence: 99%